SPECIAL ISSUE ON EMERGING TRENDS AND INNOVATIONS ACROSS MULTIDISCIPLINARY RESEARCH - R Arul; Dey, Veto; Jibril, Abdulaziz Nuhu; Heidari, Alireza; Jagtap, VD. Manoj M (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Dear Readers and Contributors, The ShodhKosh: Journal of Visual and Performing Arts invites original research papers, review articles, and creative–critical contributions for a Special Issue titled “Emerging Trends and Innovations Across Multidisciplinary Research.” In today’s rapidly evolving academic and technological landscape, research is increasingly transcending traditional disciplinary boundaries. The convergence of science, technology, humanities, arts, and management has opened new pathways for innovation, knowledge creation, and problem-solving. Multidisciplinary research not only fosters collaboration across diverse fields but also enables a more holistic understanding of complex global challenges, including sustainability, digital transformation, cultural dynamics, and socio-economic development. This Special Issue aims to explore emerging trends and innovative practices across a wide spectrum of academic disciplines. It seeks to provide a platform for scholars, researchers, and practitioners to present interdisciplinary perspectives that integrate theoretical insights, empirical findings, and creative approaches. The issue encourages contributions that highlight novel methodologies, cross-sectoral applications, and transformative ideas that bridge gaps between disciplines. Aligned with the journal’s commitment to interdisciplinary scholarship in arts, media, design, culture, and creative technologies, this Special Issue emphasizes the importance of inclusive and integrative research practices. Submissions are invited that engage with contemporary issues such as digital innovation, sustainability, cultural exchange, creative industries, technological advancements, and interdisciplinary pedagogy. We welcome submissions that demonstrate scholarly rigor, originality, and critical engagement, contributing meaningfully to the advancement of multidisciplinary knowledge and innovation in the contemporary era. Dr. R Arul Assistant Professor, Department of Commerce, St.Joseph's College (Autonomous), Tiruchirappalli, India Email: arul_cc2@mail.sjctni.edu/arulfriends2005@gmail.com Dr. Veto Dey Associate Professor, Department of Management, T.John College, Bangalore, India Email: vetodey@tjohngroup.com Dr. Abdulaziz Nuhu Jibril Department of Agricultural and Environmental Engineering, Faculty of Engineering, Bayero University Kano, Nigeria Email: anjibril.age@buk.edu.ng / abdul3787@yahoo.com Dr. Alireza Heidari Ph.D., D.Sc., Faculty of Chemistry, California South University (CSU), Irvine, California, USA Email: scholar.researcher.scientist@gmail.com VD. Manoj M Jagtap Associate Professor, Department of Rachana Sharir, YMT Ayurvedic College, Institutional Area, Sector 4, Kharghar, Navi Mumbai, Maharashtra - 410210, India Email: vdmanojjagtap@gmail.com